Family Resilience With Stunted Children Aged Below 5 Years: A Qualitative Study in Depok City, Indonesia - Dwi Cahya Rahmadiyah; Junaiti Sahar; Widyatuti; Ratu Ayu Dewi Sartika; Hamidah Hassan (SAGE Publishing, 2024)
Stunting is influenced by family and household factors that affect toddler nutrition. As the primary provider of both physical and psychological resources to prevent health problems, the family has a significant role in preventing stunting. Family resilience in supporting child health is mediated by family functioning. A qualitative descriptive study explored the influence of family resilience in fulfilling the nutritional needs of stunted children. This study involved in-depth interviews with 23 mothers of stunted children aged 24 to 59 months. Through content analysis, we identified three main themes: (1) family belief that stunting is hereditary, (2) family belief that stunted children will "grow up," and (3) lack of communication between family members in discussing stunting. Future studies should explore intervention models to increase family resilience and prevent stunting in children under five.